A preliminary assessment of the value and impact of multiple configurations of constellations of EON-MW, a proposed 12U microwave sounder CubeSat for global NWP - Yan Zhou (Taylor & Francis Group, 2021)
Observing system assessments were made for the Earth Observing Nanosatellite-Microwave (EON-MW), a 12U CubeSat analog of the Advanced Technology Microwave Sounder (ATMS). Since the EON-MW channels and sensor specifications closely follow those of ATMS, the sensor characteristics and geophysical capabilities assessments indicate that the value of information for humidity (temperature) of EON-MW observations will be similar (very similar) to that of ATMS. Eight global observing system simulation experiments (OSSEs) were carried out to evaluate several different EON-MW constellations for data gap mitigation and/or replacement of existing sensors. In these OSSEs, adding 2 EON-MW sensors in different orbits, compared to adding a single EON-MW sensor, improves forecasts generally, and improves the analysis of at least wind and humidity. In terms of the overall OSSE impacts in the scenarios considered, a single EON-MW sensor is a close substitute for ATMS and two EON-MW sensors are a close substitute for the Special Sensor Microwave Imager Sounder (SSMIS). The analysis and forecast impacts indicate that EON-MW provides improved humidity profiles compared to SSMIS and ATMS.